2010
DOI: 10.1021/bi100463d
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Characterization of the 2/2 Hemoglobin from Synechococcus sp. PCC 7002,

Abstract: Cyanobacterium Synechococcus sp. PCC 7002 contains a single gene (glbN) coding for GlbN, a protein of the 2/2 hemoglobin lineage. The precise function of GlbN is not known, but comparison to similar 2/2 hemoglobins suggests that reversible dioxygen binding is not its main activity. In this report, the results of in vitro and in vivo experiments probing the role of GlbN are presented. Transcription profiling indicated that glbN is not strongly regulated under any of a large number of growth conditions and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(94 citation statements)
references
References 62 publications
3
91
0
Order By: Relevance
“…These include four TrHb1s, Mycobacterium tuberculosis [71], Geobacillus stearothermophilus [72], and the cyanobacteria Synechocystis sp.PCC7002 [73][74] and Synechococcus sp. PCC7002 [75]; three TrHb2s, Mycobacterium tuberculosis [76], Bacillus subtilis [77] and Thermobifida fusca [78] and two TrHb3s, Campylobacter jejuni [79] and Helicobacter hepaticus [80]. The structures provide invaluable information on the choice of residues that can be fruitfully studied by site-directed mutagenesis and are critical, of course for quantum mechanical modeling of ligand access and other sub-molecular properties.…”
Section: Crystal Structuresmentioning
confidence: 99%
“…These include four TrHb1s, Mycobacterium tuberculosis [71], Geobacillus stearothermophilus [72], and the cyanobacteria Synechocystis sp.PCC7002 [73][74] and Synechococcus sp. PCC7002 [75]; three TrHb2s, Mycobacterium tuberculosis [76], Bacillus subtilis [77] and Thermobifida fusca [78] and two TrHb3s, Campylobacter jejuni [79] and Helicobacter hepaticus [80]. The structures provide invaluable information on the choice of residues that can be fruitfully studied by site-directed mutagenesis and are critical, of course for quantum mechanical modeling of ligand access and other sub-molecular properties.…”
Section: Crystal Structuresmentioning
confidence: 99%
“…Several studies of the transcriptome of Synechococcus cells have detected constitutive expression of glbN [1618]. When overexpressed under microoxic conditions, the protein contains covalently attached heme whereas oxic conditions appear to favor unmodified GlbN [16]. Thus, both GlbN and GlbN-A are candidates for physiological relevance, and the PTM may act as a sensor for cellular redox and oxygen status.…”
Section: Introductionmentioning
confidence: 99%
“…6A) and PCC 7002 (PDB ID: 4MAX [66], Fig. 6B), respectively, as well as NMR structure for PCC 7002 (PDB ID: 2KSC [67]). The combination of site-directed mutagenesis, NMR and optical spectroscopic studies provided evidence that the His-heme cross-link in reduced cyanobacteria Hbs was formed by an electrophilic addition with a reduction-driven mechanism (Scheme 4) [68].…”
Section: C-n Bondmentioning
confidence: 99%
“…It was shown that introduction of a cysteine at position 117 (H117C mutation) of PCC 6803 can result in formation of a thioether bond with the heme 2-vinyl group [68], suggesting that this position is suitable for both His-heme and Cys-heme cross-links. Despite the fact, cyanobacteria Hbs prefer the His-heme cross-link, likely due to its advantages such as less interference under high oxidative and nitrosative stress conditions that many cyanobacteria encounter [67].…”
Section: C-n Bondmentioning
confidence: 99%